Суть і місце деконструктивізму в архітектурі ХХ століття - Криворучко, Ольга Юріївна (Національний університет "Львівська політехніка", 2008)
Дисертація присвячена розкриттю сутності явища деконструкції в архітектурі, визначенню місця і ролі течії деконструктивізму в архітектурному процесі ХХ ст. У роботі виявлено передумови появи деконструктивізму в сучасній архітектурі та його ідейних і стилістичних попередників у архітектурі ХХ ст.; сформульовано критерії ідентифікації деконструктивізму; на основі зібраного матеріалу здійснено фактичну характеристику явища деконструктивізму (виявлено архітектурні об’єкти та авторів-архітекторів) і окреслено його просторові й часові межі; проаналізовано вибрані об’єкти архітектури деконструктивізму та визначено внутрішньостильову структуру течії деконструктивізму. Крім того, у дисертації вперше проаналізовано сучасну українську архітектуру на предмет присутності деконструктивізму й виявлено часткові й повні, а також псевдо-деконструктивістські об’єкти. У результаті в роботі сформульовано архітектурні принципи й ідейні пріоритети деконструктивізму. Диссертация посвящена раскрытию сути явления деконструкции в архитектуре, определению места и роли направления деконструктивизма в архитектурном процессе ХХ века. В работе выявлено предпосылки возникновения деконструктивизма в современной архитектуре и его идейных и стилистических предшественников в архитектуре ХХ века; сформулировано критерии идентификации деконструктивизма; на базе собранного материала дано фактическую характеристику явления деконструктивизма (выявлено архитектурные объекты и авторов-архитекторов) и обозначено его пространственные и временные границы; проанализировано выбранные объекты архитектуры деконструктивизма и сформулировано внутристилевую структуру направления деконструктивизма. А также в диссертации впервые проанализировано современную украинскую архитектуру на предмет присутствия деконструктивизма и выявлено частичные и полные, а также псевдо-деконструктивистские объекты. В результате в работе сформулированы архитектурные принципы и идейные приоритеты деконструктивизма. The basic idea of dissertation work was to reveal an essence of the phenomenon|phenomen| of deconstruction in architecture, finding the definition of the location and role of deconstruction flow|current| in the architectural history of ХХ century |century|. It has been found|occurring| preconditions of deconstruction architecture appearance in contemporary architecture, its ideological and stylistic predecessors|century|; the criteria of identification of deconstruction architecture were figured out. The basic|main| criterion is: the essence of deconstruction architecture lies in deconstruction|, all the architectural facilities are directed|ducted| toward its expression (an architectural object on all levels|Y-level| and in all projections must be deconstructive: building structure and slab, planning and situation scheme, every elevation should be plotted in deconstruction way). On the basis of gathered material the factual characteristic of the deconstruction was carried out: more than 300 architectural objects classified and more than 30 architects defined, the spatial and time (1970-2000-th.) boundaries of deconstruction architecture were outlined. Selected projects were analyzed and deconstructive style structure was determined. Thus it has been found outlined architectural approaches and ideological majorities of deconstruction architecture. Ideologically, deconstruction is architecture of protest, which argues against architecture of mainstream, against its technical and aesthetical boundaries and limits. But deconstruction architecture is|appear| more aesthetical rebel than technical or structural. An application of cutting edge technologies in combination of idea and abstract language|speech| of artistic expression becomes the priority point for deconstruction. For the first time in this work modern Ukrainian architecture was analyzed for the impact of deconstruction and it has been found: some appearance of deconstruction in separate elements, details, interiors; appearance of presence of pseudo deconstructive architecture (created as a result of coping of some elements from architecture of deconstruction, without conceptual understanding), appearance in the buildings which are qualified to criteria of deconstruction architecture. The substantive provisions of thesis can be used for preparation of works of the history of the contemporary architecture; in an educational process|Carbro| – in the course and diploma|degree| planning; at planning of buildings and structures|erection, urban objects, taking into account the newest architectural achievements; methodology vallecula of architectural design process.
Суть и место деконструктивизма в архитектуре ХХ века
Essence and place of deconstruction in architecture of ХХ Century
Keywords: deconstructive architecture; deconstruction, architectural process of ХХ-th century; contemporary architecture; architectural principles; structure of style; деконструкция; деконструктивизм; архитектурный процесс; ХХ век; современная архитектура; архитектурные принципы; идейные приоритеты; внутристилевая структура; деконструкція; деконструктивізм; архітектурний процес; ХХ століття; сучасна архітектура; архітектурні принципи; ідейні пріоритети; внутрішньостильова структура